Caracterización de salud oral en escolares. Sector 1. Riobamba, 2021. - Jiménez Bonilla, Joel Alexis (2022)
The objective of this study was to analyze the level of personal oral health knowledge, as teachers and parents of schoolchildren in sector 1 of Riobamba, as well as to investigate the socio-family influence on the oral health status of students. The methodology of the investigation was descriptive cross-sectional, the study group was made up of 100 students with their own family representative and 4 teachers from the educational institutions of sector 1 of Riobamba, the technique used was observation and the instruments medical records and questionnaires of knowledge towards schoolchildren, teachers and representatives were applied, with the tabulated information from the medical records, the DMFT index and the O'Leary plaque index were calculated, on the other hand, questionnaires collected about the level of knowledge of the actors. Results showed a regular knowledge of both schoolchildren and teachers; in addition, there was no relationship between the type of diet of the schoolchildren with the DMFT index (p=0.802) and the DMFT index (p=0.904). It was concluded that knowledge of oral health was not associated with the cleaning habits practiced by schoolchildren, since the level of the DMFT index had low risk in 96% of the population, while the level of the plaque index was acceptable in 68% of schoolchildren.